Methods for Developing the Skills of Depicting Color and Light in Grades 5–7 - Aslonov Furqat Botirovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article examines methodological approaches to developing students’ skills in depicting color and light in fine arts lessons for grades 5–7. The study highlights the importance of perception, imagination, and artistic thinking in forming visual literacy and creative expression. Modern pedagogical technologies such as digital visualization, interactive learning, and project-based activities are analyzed as effective tools to enhance students’ understanding of color harmony, tonal contrast, and the interplay of light and shadow.